Isolation enhancement of densely packed array antennas with periodic MTM‐photonic bandgap for SAR and MIMO systems. Issue 3 (19th December 2019) - Alibakhshikenari, Mohammad; Virdee, Bal S.; Shukla, Panchamkumar; See, Chan H.; Abd‐Alhameed, Raed A.; Falcone, Francisco; Quazzane, Karim; Limiti, Ernesto
Abstract : A metamaterial photonic bandgap (MTM‐PBG) periodic structure is used as a decoupling frame to improve the isolation between transmit–receive (T/R) sections of the densely packed array antenna in synthetic aperture radar (SAR) and multiple‐input–multiple‐output (MIMO) systems. With this technique the MTM‐PBG structure is shown to effectively suppress surface wave propagations between the T/R array antennas by an average of 12 dB. MTM‐PBG layer comprises a periodic arrangement of dielectric circles etched in the cross‐shaped microstrip frame that is inserted between the radiating elements. Unlike other recently reported methods, the advantages of the proposed technique are: (i) simplicity; (ii) cost effectiveness as there is no need for short‐circuited via‐holes or three‐dimensional metal walls; and (iii) can be retrofitted in existing array antennas. The proposed T/R array antennas were designed to operate over an arbitrary frequency range (9.25–11 GHz) with a fractional bandwidth of 17.28%. With this technique (i) the side‐lobes are reduced; (ii) there is minimal effect on the gain performance; and (iii) the minimum edge‐to‐edge gap between adjacent radiating elements can be reduced to 0.15 λ at 9.25 GHz.